ComparisonofGenerationXandGenerationYforLeadershipStylePreferencewiththeModeratingRoleofLegacyBeliefs (Journal of Asian Development Studies, 2024)
Each generation has unique characteristics influenced by their respective historical periods. This research has explored the differences in leadership style preferences between generation X and generation Y,taking into accountthe impact of legacy belief. Legacy belief is an important measure that shows how individuals justify theiractions,andbecome more significant as they progress in their careers. By conducting a survey using random sampling,data was gatheredfrom 304 banking professionals in Islamabad, Pakistan. Results show distinct differences in the leadership approaches of generation X and generation Y, particularly in transactional and transformational styles.It was also foundthat legacy belief plays a role, with generation X individuals showing more respect for their beliefs. This study highlights the differences in leadership tendencies across generations, contributing to existing research on how they affectorganizationsand employee performance. Tailored strategies are needed to engage older employees more actively. Additionally, we suggest including Generation Z in generational studies and exploring other factors that can influence generational dynamics in the workplace